1992
DOI: 10.1042/bj2870509
|View full text |Cite
|
Sign up to set email alerts
|

Iron and aluminium in relation to brain ferritin in normal individuals and Alzheimer's-disease and chronic renal-dialysis patients

Abstract: Ferritin has been isolated and its subunit composition, iron and aluminium content determined in the cerebral cortex and cerebellum of normal individuals and in the cerebral cortex of Alzheimer's-disease and renal-dialysis patients. An e.l.i.s.a. for ferritin has been developed and the ferritin, non-haem iron and aluminium content of the parietal cortex were determined in normal individuals and Alzheimer's-disease patients. It was found that ferritin from the cerebral cortex and cerebellum of normal individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(60 citation statements)
references
References 33 publications
3
55
1
Order By: Relevance
“…Both proteins were in the iron-loaded form. Ferritin normally contains some complexed aluminum (Dedman et al, 1992), which can modulate its properties (Fleming and Joshi, 1991). Transferrin has a high affinity for, and may transport aluminum into the central nervous system (CNS) (Roskams and Connor, 1990).…”
Section: Molecular and Chemical Neuropathologymentioning
confidence: 99%
“…Both proteins were in the iron-loaded form. Ferritin normally contains some complexed aluminum (Dedman et al, 1992), which can modulate its properties (Fleming and Joshi, 1991). Transferrin has a high affinity for, and may transport aluminum into the central nervous system (CNS) (Roskams and Connor, 1990).…”
Section: Molecular and Chemical Neuropathologymentioning
confidence: 99%
“…3 A growing body of data suggests that brain iron accumulation in vivo may contribute to tissue damage in a variety of chronic neurological disorders. Histological and magnetic resonance imaging (MRI) data have suggested increases in iron levels in the gray matter in Parkinson's disease (PD), 4 -10 Alzheimer's disease (AD), [11][12][13][14][15][16][17] multiple sclerosis (MS), 18 -21 and a host of other chronic neurological disorders. 22 Consequently, there is a growing interest in optimizing the ability of MRI to estimate iron deposition in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…By the way, the mechanism behind the Al complex formation in vivo is still controversial also because two different ranges of Al bound to ferritin have been generally found: few atoms in some studies 5,6 and hundreds or even thousands in others. 3,4,9 Furthermore in this latter case also a very high Al/Fe molar ratio has been observed (in some specific case up to 6).…”
mentioning
confidence: 99%
“…4 Subsequent studies carried on ferritin isolated from brain of renal dialysis patients showed an amount of 10 Al atoms per ferritin molecule. 5 Ward et al reported a small amount of the radioactive tracer 26 Al associated with liver ferritin of Al loaded rat. 7 The total Al amount per ferritin molecule found in the these studies is of the same order as the one shown in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation